PENGARUH LAMA PENGERINGAN MENGGUNAKAN OVEN TERHADAP KARAKTERISTIK FISIKO- KIMIA ”˜KERIPIK TERUNG - Hardoko Hardoko; Hilman Fajar Sebastian (FaST : Jurnal Sains dan Teknologi, 2019)
”˜Terung’ (Sea Cucumber) chips, one of the most popular traditional products in Indonesia, are the result of the process of drying sea cucumbers with sunlight and frying. Drying problems arise during the rainy season. The purpose of this study was to determine the effect of drying using an oven temperature of 60oC on the physical and chemical characteristics of sea cucumber chips. The research method used was a long drying experimental method (0 hours, 4 hours, 8 hours, 12 hours) and observational data were analyzed with Anova at a 95% confidence level. The results showed that the drying time treatment significantly affected the water content, protein content, fat content, ash content, swelling power, but did not significantly affect the power of sea cucumber chips. The best drying time is the drying time of 12 hours which produces sea cucumbers chips which are characterized by 58.90% protein content, 1.25% water content, 20.09% fat content, 9.61% ash content, 70.19%  swelling power,  and 3.85 N/m2power broken.